Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1522-2594(199912)42:6<1137::aid-mrm19>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and dynamics of laser‐polarized 129Xe magnetization in vivo

Abstract: The first magnetic resonance imaging studies of laser-polarized 129 Xe, dissolved in the blood and tissue of the lungs and the heart of Sprague-Dawley rats, are described. 129 Xe resonances at 0, 192, 199, and 210 ppm were observed and assigned to xenon in gas, fat, tissue, and blood, respectively. One-dimensional chemical-shift imaging (CSI) reveals xenon magnetization in the brain, kidney, and lungs. Coronal and axial twodimensional CSI show 129 Xe dissolved in blood and tissue in the thorax. Images of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 0 publications
5
96
0
1
Order By: Relevance
“…Clearly, hyperpolarized Xe129, transported through the vasculature, was concentrated in the region of the nodule over the course of the breath-hold acquisition. The signal contribution from Xe129 in the blood that has traveled to a location distant from the airspaces, such as to a solid lesion or the major vessels and heart, should depend on the frequency and amplitude of radiofrequency excitation (6,9,10). Thus, by selecting appropriate acquisition parameters, it should be possible to highlight Xe129 that has just dissolved in tissue versus Xe129 that has been transported away from the airspaces.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, hyperpolarized Xe129, transported through the vasculature, was concentrated in the region of the nodule over the course of the breath-hold acquisition. The signal contribution from Xe129 in the blood that has traveled to a location distant from the airspaces, such as to a solid lesion or the major vessels and heart, should depend on the frequency and amplitude of radiofrequency excitation (6,9,10). Thus, by selecting appropriate acquisition parameters, it should be possible to highlight Xe129 that has just dissolved in tissue versus Xe129 that has been transported away from the airspaces.…”
Section: Discussionmentioning
confidence: 99%
“…Two 12gXeCSIS It is interesting to note that in this study, only one resonance was observed that could be assigned to blood in the 129XeIWIR. spectra (with a chemical shift of w21O ppm, obtained, for example, from localized NMR spectroscopy from the rat's heart region) [233]. This result suggests that under the conditions of their experiment (e.g., xenon dissolved in rat blood in vivo at 37 "C and 2 T) the xenon exchange between RBCS and plasma was contrast to the previous in vitro fast with respect to the the NMR time scale, in results involving xenon in human blood at higher fields and ambient conditions [224,225].…”
Section: Enhanced Nmr and Mri Of Tissues 210mentioning
confidence: 97%
“…following respiration of laser-polarized xenon by laboratory rats [233]. Two 12gXeCSIS It is interesting to note that in this study, only one resonance was observed that could be assigned to blood in the 129XeIWIR.…”
Section: Enhanced Nmr and Mri Of Tissues 210mentioning
confidence: 99%